2014
DOI: 10.1590/1413-81232014197.17322013
|View full text |Cite
|
Sign up to set email alerts
|

A Atenção Primária à Saúde e seus atributos: a situação das crianças menores de dois anos segundo suas cuidadoras

Abstract: A Atenção Primária à Saúde e seus atributos: a situação das crianças menores de dois anos segundo suas cuidadorasPrimary health care and its attributes: the situation of children under two years of age according to their caregivers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
1
37

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 9 publications
8
33
1
37
Order By: Relevance
“…The small number of nutritionists, especially those enrolled in FHSC, who indicated having participated in training to work in the PHC, in the nutrition actions directed to the Primary Care and in the child's health converges with previous reports [18][19][20]. However, complementary analyzes of the current study did not identify differences in the knowledge of technical materials nor in the performance of actions of the nutrition area among those with and without graduate courses (data not shown).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The small number of nutritionists, especially those enrolled in FHSC, who indicated having participated in training to work in the PHC, in the nutrition actions directed to the Primary Care and in the child's health converges with previous reports [18][19][20]. However, complementary analyzes of the current study did not identify differences in the knowledge of technical materials nor in the performance of actions of the nutrition area among those with and without graduate courses (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the demographic profile, the predominance of female nutritionists and in the age groups between 20-39 years is comparable to that verified in other studies, which revealed the feminization of the profession and the performance of young adults [9,[16][17][18]. This profile may be related to the cultural connotation, in Brazil, of the role of women as caregivers [19] and the short time of existence of the profession [16].…”
Section: Discussionsupporting
confidence: 82%
“…In most educational institutions of healthcare professionals (nurses, doctors etc. ), health education is defined in a purely clinical education and biomedical paradigm (24) . This approach favors the onset of problems such as the distance of the professional from the patient and their family, difficulties in understanding the dialogue between those involved and denial/rejection of knowledge coming from patients.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional public health is constituted by the image and similarity of technoscience and the biomedical model, and is still ingrained in the practices of health care professionals (21) . Some authors correlate this problem to the difficulty in obtaining qualified professionals working in the ESF model and to rethink the issue of health promotion depending on the educational practices, as highlighted by the assumptions of APS (22)(23)(24)(25) . This situation happens as a result of the training model of these professionals: hospital centric, biologistic and fragmented (24) .…”
mentioning
confidence: 99%
“…Assim, o processo de implantação do SUS, direcionado por seus princípios e pelo conceito de saúde como produção social, compõe o contexto de ressignificação do trabalho do enfermeiro no âmbito da Atenção Primária à Saúde (17) . Vale salientar, ainda, que dentre os diversos campos de atuação da saúde, a Estratégia Saúde da Família (ESF) oportuniza um espaço privilegiado para a aplicação diferenciada das práticas de cuidado (18) . Nesse prisma, a análise de cada um dos atributos da APS, a partir da percepção dos usuários da APS, revelou melhores escores para as equipes com melhor formação (residência), com diferenças estatisticamente significantes para os atributos de acessibilidade (p=000), longitudinalidade (p=0,040), coordenação-sistema de informações (p=0,000) serviços disponíveis e serviços integrados (p=0,000), além de orientação familiar e comunitária (p=0,000).…”
Section: Métodosunclassified